Permafrost-related hiatuses in stalagmites: Evaluating the potential for reconstruction of carbon cycle dynamics - Lechleitner, Franziska A.; Mason, Andrew J.; Breitenbach, Sebastian F. M.; Vaks, Anton; Haghipour, Negar; Henderson, Gideon M. (Quaternary Geochronology, 2020)
ISSN:1871-1014